Tourism and Economic Growth: The case of Next 11 Countries - Kum, Hakan; Aslan, Alper; Gungor, Merve (International Journal of Economics and Financial Issues, 2015)
The aim of this paper is to analyse the relationship between tourism activity and economic growth for Next-11 countries. It is concluded that there is a long run relationship between tourist arrivals and GDP and tourism arrivals has positive effect on GDP growth in N-11 countries. We find that a unidirectional causality from economic growth to tourism is valid confirming Economic Driven Tourism Growth Hypothesis. Keywords: Tourism development; Economic growth; Causality; N-11 JEL Classifications: F43; L83